2020
DOI: 10.1016/j.ebiom.2020.102991
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Zika virus infections are enhanced by live attenuated dengue vaccine but not by recombinant DSV4 vaccine candidate in mouse models

Abstract: Background A tetravalent live attenuated dengue vaccine, Dengvaxia, sensitised naïve recipients to severe dengue illness upon a subsequent natural dengue infection and is suspected to be due to antibody-dependent enhancement (ADE). ADE has also been implicated in the severe neurological outcomes of Zika virus (ZIKV) infection. It has become evident that cross-reactive antibodies targeting the viral pre-membrane protein and fusion-loop epitope are ADE-competent. A pre-clinical tetravalent dengue su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…However, unlike the ICs made with 3H5 mAb, the ICs generated with 4G2 mAb revealed potent lethality in the denguesensitive AG129 mouse, without enhancing serum viremia. This finding is further affirmed with a recent report published in EBioMedicine by Shukla et al (2020). The investigators showed that both Dengue and Zika virus infections are enhanced by live attenuated dengue vaccine that majorly elicits FL and prM crossreactive antibodies but not by a recombinant tetravalent Dengue Subunit Vaccine candidate, capable of inducing predominantly EDIII directed type-specific antibodies in the absence of antibodies to FL and prM epitopes in murine models.…”
Section: Ade: In Vitro Vs In Vivo Assayssupporting
confidence: 71%
See 2 more Smart Citations
“…However, unlike the ICs made with 3H5 mAb, the ICs generated with 4G2 mAb revealed potent lethality in the denguesensitive AG129 mouse, without enhancing serum viremia. This finding is further affirmed with a recent report published in EBioMedicine by Shukla et al (2020). The investigators showed that both Dengue and Zika virus infections are enhanced by live attenuated dengue vaccine that majorly elicits FL and prM crossreactive antibodies but not by a recombinant tetravalent Dengue Subunit Vaccine candidate, capable of inducing predominantly EDIII directed type-specific antibodies in the absence of antibodies to FL and prM epitopes in murine models.…”
Section: Ade: In Vitro Vs In Vivo Assayssupporting
confidence: 71%
“…Moreover, enhanced ZIKV infection were observed in several organs of Stat2 −/− mice inoculated with anti-Dengvaxia and anti-TV DENV sera. However, DSV4-induced anti-serum neither cross-neutralized ZIKV in vitro nor promoted ADE in vivo (Shukla et al, 2020). The pre-immunity against ZIKV is also a serious concern for developing the dengue vaccine.…”
Section: Denv/zikv Interaction and Adementioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that suboptimal vaccine protection is a more likely explanation for incidences of breakthrough viremia. It is important to note that other studies have detected elevated ZIKV viral loads after challenge in both plasma and tissues, following passive transfer of anti-DENV immune sera from humans or previously DENV immunized BALB/c mice into both STAT2 -/- and CD11c- Ifnar1 -/- mouse models [ 23 ]. These data attest that the specific mouse strain used, due to differences in pathogenesis, viral tropism, and susceptibility, may affect the magnitude of ZIKV disease enhancement observed.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies conducted over the 1970s−80s established in vitro ADE for the global pathogen Dengue virus (DEN), as well as identified the role for Fc-Receptor (Fc-R) engagement in ADE via studies with other flaviviruses (27)(28)(29). By the 1990s, ADE was recognized as a factor in severe DEN disease (Haemorrhagic Fever, Shock Syndrome), on subsequent infection with a DEN serotype different to the original case (30), which has also frustrated attempts to develop a DEN vaccine (31). Many virus families have been observed as displaying enhanced in vitro growth post-infection due to ADE, but the impact in vivo and on disease manifestation are not currently well-understood (32)(33)(34).…”
Section: Antibody-dependent Enhancementmentioning
confidence: 99%